2003
DOI: 10.1086/375533
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Emission from the Hot Interstellar Medium and Southwest Radio Lobe of the Nearby Radio Galaxy Centaurus A

Abstract: We present results from two Chandra/ACIS-I observations and one XMM-Newton observation of X-ray emission from the ISM and the inner radio lobes of the nearby radio galaxy Centaurus A. The ISM has an average radial surface brightness profile that is well described by a β-model profile with index β=0.40±0.04 and a temperature of k B T ISM ∼0.29 keV beyond 2 kpc from the nucleus. We find that diffuse X-ray emission is coincident with the outer half of the southwest radio lobe, and a bright X-ray enhancement is de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
158
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(173 citation statements)
references
References 106 publications
11
158
4
Order By: Relevance
“…Van Gorkom et al (1990) reached a similar conclusion when comparing H i dynamical mass estimates with the X-ray estimates. However, Kraft et al (2003) recently used Chandra and XMM data to measure the total gravitating mass with 15 kpc and determined a value of $2 Â 10 11 M , which is statistically indistinguishable from the values we obtain from our mass models within the same radius. This independent mass determination implies that our assumptions of orbital isotropy and a high inclination for the stellar disk are not likely to be grossly wrong, at least within 15 kpc.…”
Section: Mass-to-light Ratiocontrasting
confidence: 52%
“…Van Gorkom et al (1990) reached a similar conclusion when comparing H i dynamical mass estimates with the X-ray estimates. However, Kraft et al (2003) recently used Chandra and XMM data to measure the total gravitating mass with 15 kpc and determined a value of $2 Â 10 11 M , which is statistically indistinguishable from the values we obtain from our mass models within the same radius. This independent mass determination implies that our assumptions of orbital isotropy and a high inclination for the stellar disk are not likely to be grossly wrong, at least within 15 kpc.…”
Section: Mass-to-light Ratiocontrasting
confidence: 52%
“…This is the largest galactocentric distance in an early-type galaxy for which dark matter is not necessary to explain its internal kinematics. The obtained value of the massto-light ratio (6.24 < ∼ M/L B < ∼ 7.00) agrees with the value inferred from the X-rays (Kraft et al 2003). In the outer region of NGC 5128, 7 < r < 14R e (= 78 arcmin) we encountered an increasing velocity dispersion, which implies an increase of the mass-to-light ratio (or tangential anisotropies) implying certain amounts of dark matter in these regions (if any).…”
Section: Newtonian Mass-follows-light Modelssupporting
confidence: 88%
“…They found that the ISM has an average radial surface brightness profile that is well described by a β-model profile with the index β = 0.40 ± 0.04 and a temperature of k B T ISM = 0.29 keV beyond 2 kpc from the galactic nucleus. Kraft et al (2003) calculated that within 15 kpc of the nucleus the total mass of NGC 5128 is ∼2 × 10 11 M . This value corresponds to the massto-light ratio M/L B = 6.70 at 15 kpc (= 2.44R e , which is a region which contains 75 per cent of the total light for de Vaucouleurs law).…”
Section: X-ray Data For Ngc 5128mentioning
confidence: 99%
“…As the only FR I-type radio galaxy whose X-ray emission is heavily obscured and dominated by an accretion flow, its nuclear X-ray emission is more similar to that of the FR II-type sources. One possible resolution of this problem is that the recent merger that has occurred in Cen A may have provided additional material to accrete onto the supermassive black hole, triggering heightened nuclear activity and a new phase of radio activity, causing the supersonic reinflation of the lobes (Kraft et al 2003).…”
Section: Model 3: An Intrinsic Dichotomy Exists In the Accretion Flowmentioning
confidence: 99%